Pain therapy with oxycodone/naloxone prolonged-release combination: case report - Błaszczyk, Feliks; Droń, Aleksandra (Contemporary Oncology/Współczesna Onkologia, 2013)
Pain afflicts patients suffering from many chronic diseases and is present in 80% of cases of patients with advanced cancer who suffer from persistent pain. The aim of the pain treatment is to achieve the maximum analgesic effect while minimizing side effects. The main analgesic agent – morphine is unfortunately a therapy associated with gastrointestinal side effects. It appears that the combination of oxycodone and naloxone available as Targin® (Mundipharma) is an alternative. The paper presents a case of a 45-year-old patient who was treated effectively with oxycodone/naloxone prolonged-release tablets. This treatment has proven to be effective in providing pain and constipation control.